HOW COULD THE CREDIBILITY OF THE HARRIS–TODARO MODEL BE IMPROVED?. Issue 3 (8th November 2017) - Chaudhuri, Sarbajit
Abstract : A damaging property of the two‐sector, mobile capital Harris–Todaro model (known as the Corden–Findlay model) is that growth in capital (labor) endowment accentuates (mitigates) urban unemployment in a dual economy, limiting the model's applicability to the field of trade and development. To resolve this problem, we introduce the informal credit market, which provides consumption loans to rural workers during the lean season. The informal interest rate is endogenously determined from the maximizing behavior of the informal sector lender. Factor accumulations produce their expected results on the absolute level of urban unemployment, while poverty eradication programs raise the informal interest rate and diminish borrowers' welfare under a wide range of parametric values. Finally, a wage subsidy policy to the urban sector unambiguously lowers the informal interest rate. Urban unemployment decreases while worker welfare improves under reasonable conditions. The result on unemployment is contrary to results of the Corden–Findlay model.